1997
DOI: 10.1007/bf02303799
|View full text |Cite
|
Sign up to set email alerts
|

Localizing the sentinel node in cutaneous melanoma: Gamma probe detection versus blue dye

Abstract: The gamma probe together with PBD can identify more SNs (99.5%) than lymphatic mapping with PBD alone (84%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(77 citation statements)
references
References 14 publications
3
66
0
8
Order By: Relevance
“…24,25 When using only PBD, the literature has registered a lower identification rate for the SN (85%) than with GPD (98-100%). [26][27][28][29] Similar data were obtained in our study (PBD = 76% and GPD = 97%). Subgroup analysis of the basins showed that GPD and PBD identified 100% of the inguinal SN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…24,25 When using only PBD, the literature has registered a lower identification rate for the SN (85%) than with GPD (98-100%). [26][27][28][29] Similar data were obtained in our study (PBD = 76% and GPD = 97%). Subgroup analysis of the basins showed that GPD and PBD identified 100% of the inguinal SN.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors have questioned whether there is any role for PBD in the SN biopsy, 27 emphasizing the role of GPD in the outpatient clinic. Others indicate PBD as a standard procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative sentinel node identification traditionally relies on the combination of acoustic signals generated by a g-ray detection probe and optical sentinel node visualization using a visible blue dye (12,13). Because the probe has a limited spatial resolution and sentinel nodes do not always stain blue, sentinel nodes can be difficult to localize in areas with a complex anatomy and when sentinel nodes are near the injection site (14,15).…”
mentioning
confidence: 99%
“…9,10 An additional technique, intraoperative use of the gamma probe, permits surgeons to evaluate intervening regions between the primary tumor and the standard lymph node basin and to identify SLNs in unusual locations. 3,5,[11][12][13][14] The significance of SLNs located in these unusual locations, however, has not been established completely. If these SLNs harbor metastatic disease, failure to evaluate them would lead to understaging the patient, alter treatment recommendations (i.e., the patient may not be offered indicated adjuvant therapy), and may result in an increased risk of regional or distant recurrence.…”
mentioning
confidence: 99%